Teacher Competency Improvement: Training and Assistance in Mapping Learning Outcomes, Learning Objectives, Flow of Learning Objectives for the Merdeka Curriculum - Adikara, Fahmi Surya; Mansur, Nabilah; Nurani, Dwi Cahaya; Pulungan, Marwan; Astika, Ruri Tria; Susiloningsih, Esti; Fathia, Najlatul (Pascasarjana Universitas Mataram, 2024)
The quality of teaching in elementary schools is a crucial factor that influences the early development of students. Training and mentoring for elementary school teachers are expected to strengthen teacher capacity in terms of mapping learning outcomes, learning objectives, and learning objective flows. Community service activities are carried out using the Participatory Action Research (PAR) method. The stages of activities that will be carried out by the community service program team are as follows: (1) giving an initial test (pre-test); (2) implementing offline community service; (3) online mentoring; (4) evaluation and reflection; and (5) giving a final test (post-test). The pre-test score with 20 participants obtained an average of 51.75, while the post-test score obtained an average of 90, so that the N-Gain score was 0.79. This value represents an interpretation of a high improvement category. Overall, this community service activity was able to improve the knowledge and understanding of elementary school teachers in Prabumulih City in mapping CP, TP, and ATP in accordance with the independent curriculum.